Risk factors for and outcomes of poststroke pneumonia in patients with acute ischemic stroke treated with mechanical thrombectomy - Zhang, Ping; Chen, Lei; Jiang, Yi; Yuan, Hui; Zhu, Xuan; Zhang, Minmin; Wu, Tao; Deng, Benqiang; Yang, Pengfei; Zhang, Yongwei; Liu, Jianmin (Frontiers in Neurology, 2023)
Objective The purpose of the study was to assess the risk factors for poststroke pneumonia (PSP) and its association with the outcomes in patients with acute ischemic stroke (AIS) due to large artery occlusion treated with mechanical thrombectomy (MT). Methods Consecutive patients with AIS who underwent MT from January 2019 to December 2019 in the stroke center of Changhai Hospital were identified retrospectively. All of the patients were evaluated for the occurrence of PSP while in the hospital, and their modified Rankin scale (mRS) scores were assessed 90 days after having a stroke. Logistic regression analysis was conducted to determine the independent predictors of PSP, and the associations between PSP and clinical outcomes were analyzed. Results A total of 248 patients were enrolled, of whom 33.47% (83) developed PSP. Logistic regression analysis revealed that body mass index (BMI) [unadjusted odds ratio (OR) 1.200, 95% confidence interval (CI) 1.038–1.387; p = 0.014], systemic immune-inflammation index (SII) (OR 1.001, 95% CI 1.000–1.002; p = 0.003), dysphagia (OR 9.498, 95% CI 3.217–28.041; p < 0.001), and intubation after MT (OR 4.262, 95% CI 1.166–15.581; p = 0.028) were independent risk factors for PSP. PSP was a strong predictor of clinical outcomes: it was associated with functional independence (mRS score ≤ 2) (OR 0.104, 95% CI 0.041–0.260; p < 0.001) and mortality at 90 days (OR 3.010, 95% CI 1.068–8.489; p = 0.037). Conclusion More than one in three patients with AIS treated with MT developed PSP. Dysphagia, intubation, higher BMI, and SII were associated with PSP in these patients. Patients with AIS who develop PSP are more likely to experience negative outcomes. The prevention and identification of PSP are necessary to reduce mortality and improve clinical outcomes.